Enhancing software quality of CI/CD pipeline through continuous testing: a DevOps-driven maintainable hybrid automation testing framework - Patel, Akshit Raj; Tyagi, Sulabh (International journal of information technology (Singapore. Online), 2025)
The rapid adoption of DevOps methodologies has revolutionized software development by enabling Continuous Integration and Continuous Deployment (CI/CD). However, ensuring efficient, scalable, and maintainable automated testing remains a significant challenge in DevOps-driven environments. This study introduces the Maintainable Hybrid Test Automation Framework (MHTAF), designed to enhance test efficiency, reliability, and code quality. MHTAF leverages the Page Object Model (POM) to promote test script reusability and integrates key DevOps tools, including Selenium for test automation, Jenkins for CI/CD management, SonarQube for continuous code quality assessment, and Docker for containerized deployment. To evaluate the framework, we implemented MHTAF on two large-scale e-commerce platforms, Amazon and Flipkart. Experimental results demonstrate significantly reduced code duplication, improved test execution efficiency, and enhanced maintainability within CI/CD pipelines. Our findings highlight MHTAF’s effectiveness in streamlining test automation while ensuring high software quality in dynamic DevOps environments.